ChemInform Abstract: Phosphorus(V)‐Catalyzed Deoxydichlorination Reactions of Aldehydes. Issue 6 (11th February 2014) - An, Jie; Tang, Xiaoping; Moore, Joshua; Lewis, William; Denton, Ross M.
Abstract The conversion of aldehydes into geminal dichlorides proceeds via a phosphorus(V)‐catalysis manifold in which phosphine oxide turnover is induced by using oxalyl chloride as a consumable reagent.